Circular RNA in hepatocellular carcinoma: emerging therapeutic strategies - Jazbec, Gregor; Režen, Tadeja (Frontiers in Immunology, 2025)
Circular RNAs, or circRNAs, are unique single-stranded RNA molecules that form covalently closed circles. They possess a wide range of cellular functions and can act as tumor suppressors or promoters, regulating various aspects of carcinogenesis. These functions include acting as microRNA sponges, interacting with and binding to proteins and mRNA, regulating transcription and RNA splicing, translating into proteins, and serving as cargo in exosomes. Due to their diverse cellular roles and enhanced molecular stability, circRNAs are not only promising biomarkers but also emerging candidates for the development of RNA-based therapeutics. In this review, we explored the therapeutic potential of circular RNA by reviewing the current state of the art in the field of oncology, with a particular focus on hepatocellular carcinoma. Based on their endogenous functions, circular RNA can be designed, synthesized and delivered to produce various proteins, such as neoantigens and cytokines, or to sequester oncogenic microRNA in tumor cells. Although many therapeutic applications of circular RNA are still in the early stages of development, they have already shown promising results in both in vitro and in vivo animal models. In summary, circular RNAs are emerging as both therapeutics and biomarkers in liver cancer and broader oncology, with relevant clinical applicability, particularly in immunotherapy.